Antioxidant activities and hepatoprotective potential of Dracocephalum rupestre Hance extract against CCl4‐induced hepatotoxicity in Kunming mice. Issue 2 (7th December 2017) - Zhu, Chang‐San; Liu, Kun; Wang, Jun‐Li; Li, Jian‐Fei; Liu, Ming‐Fei; Hao, Na; Lin, Yu‐Xing; Xiao, Ze‐Feng
Abstract: The current study evaluated antioxidant activity of Dracocephalum rupestre Hance, characterized by the polyphenolic compounds in the ethyl acetate fraction (EAF) from D. rupestre and investigated the protective mechanisms of EAF in carbon tetrachloride (CCl4 )‐induced hepatic injury. EAF showed the largest antioxidant capacity as demonstrated by DPPH, ABTS, OH, and FRAP assays ( p  ≤ .05). Using LC–MS, two polyphenolics, for example, rosmarinic acid, and eriodictyol were identified in EAF. Total phenol content of D. rupestre was correlated significantly with FRAP value ( r  = .999, p  ≤ .001). The results also showed that EAF decreased serum ALT and AST activities compared with model group, as well as the histological findings. In addition, EAF remarkably decreased MDA and LDH levels in liver. This is the first time to reveal the hepatoprotective effect of EAF from D. rupestre, which may be developed as a new drug for treatment of liver injury in future. Practical applications: Dracocephalum rupestre Hance is known as Chinese herbal medicine with pharmacological functions of antioxidant, anti‐inflammatory and has been mainly used in the treatment of damp‐heat, headache, fever, jaundice, hepatitis, liver toxicity, and other diseases. In order to detect the potential application of this plant, the antioxidant and hepatoprotective activities of D. rupestre were investigated. It was found that the ethyl acetate fraction (EAF) from D. rupestre displayed strong antioxidant activity. We also demonstrate that EAF could lessen CCl4 ‐induced acute liver injury in mice. Also, rosmarinic acid may play an important role in the antioxidant activity and hepatoprotective effect for EAF.